Students Proportional Reasoning Level in Solving Ill Structured Problem on Proportion Material in Terms of Gregorc’s Thinking Style - Pramono, Yasmine Az Zahra Awwalina; Abdussakir, Abdussakir; Irawan, Wahyu Henky; Sujarwo, Imam (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2025)
This study examines the level of proportional reasoning in students when solving ill-structured problems concerning proportions, in terms of Gregorc's cognitive styles. A qualitative approach was used, involving 8 participants from grade VIII-B of MTsN Kota Batu. Based on the analysis, it can be concluded that students' cognitive styles affect their understanding of proportional reasoning. Students with a concrete sequential (CS) thinking style showed difficulty in understanding the concept of proportional and still relied on trial-and-error approaches, indicating they are at Level 0 (Non-proportional reasoning). Students with a abstract sequential (AS) and concrete random (CR) thinking style have used some visual or concrete aids, although they have not fully transitioned to a more systematic mathematical approach, placing them at Level 1 (Manipulative Proportional Reasoning). Meanwhile, students with an abstract random (AR) thinking style were able to use mathematical models to solve proportional problems but still faced challenges in consistently applying the correct method, leading them to Level 3 (Pre-multiplicative Proportional Reasoning). The differences in students' cognitive styles affect how they understand and apply the concept of proportional reasoning, including their ability to choose the appropriate method and maintain consistency in its application.